The Role of Low-Level Laser in Periodontal Surgeries - Sobouti, Farhad; Khatami, Maziar; Heydari, Mohaddase; Barati, Maryam (Journal of Lasers in Medical Sciences, 2015)
Treatment protocols with low-level Laser (also called ‘soft laser therapy) have been used in health care systems for more than three decades. Bearing in mind the suitable sub-cellular absorption and the cellular-vascular impacts, low-level laser may be a treatment of choice for soft tissues. Low-level lasers have played crucial and colorful roles in performing periodontal surgeries. Their anti-inflammatory and painless effects have been variously reported in in-vitro studies. In this present review article, searches have been made in Pub Med, Google Scholar, and Science Direct, focusing on the studies which included low-level lasers, flap-periodontal surgeries, gingivectomy, and periodontal graft. The present study has sought to review the cellular impacts of low-level lasers and its role on reducing pain and inflammation following soft tissue surgical treatments.